1984
DOI: 10.1002/hep.1840040506
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Serum N-Terminal Propeptide of Collagen Type III Levels in Patients with Chronic Liver Disease†

Abstract: To evaluate the diagnostic and prognostic significance of the N-terminal propeptide of collagen Type III (Col 1-3) in chronic liver disease, the peptide level was measured in the serum of 4 patients with primary biliary cirrhosis, 5 with chronic persistent hepatitis, 12 with chronic active hepatitis, and 1 with autoimmune hepatitis, for a period of 2 to 10 years and compared with liver function and histology. In primary biliary cirrhosis, Col 1-3 peptide levels were always elevated, regardless of medical thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

1984
1984
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(24 citation statements)
references
References 6 publications
1
22
0
1
Order By: Relevance
“…A long-term follow-up study showed that serum PIIINP levels changed to reflect the progression and regression of histological changes of the liver either in their natural course or in response to treatment [14]. Similar results were observed in patients with autoimmune hepatitis treated with immunosuppressive therapy and in patients with chronic hepatitis C treated with interferon-· [15].…”
Section: Serum Markers As Tools To Follow-up and Monitor Dynamics Of supporting
confidence: 62%
“…A long-term follow-up study showed that serum PIIINP levels changed to reflect the progression and regression of histological changes of the liver either in their natural course or in response to treatment [14]. Similar results were observed in patients with autoimmune hepatitis treated with immunosuppressive therapy and in patients with chronic hepatitis C treated with interferon-· [15].…”
Section: Serum Markers As Tools To Follow-up and Monitor Dynamics Of supporting
confidence: 62%
“…17 Presence of a relative increase in collagen III is often associated with fibrosis and excessive scarring in many diseases. 12,[35][36][37] Antifibrotic effects of RGTA have been demonstrated in earlier studies. Thus, RGTA treatment decreased the production of collagen III in intestinal tissue specimens from patients with Crohn's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Ele vated serum concentrations of HA have been found in various diseases such as rheumatoid arthritis [3], psoria sis [4], and liver diseases where it has been suggested to be a marker of hepatic fibrosis [5]. Recently, Hallgren et al [6] reported elevated serum concentrations of HA also in patients with renal failure which we have con firmed in a preliminary report [7], Procollagen III amino terminal propeptide (PIIINP), liberated during the conversion of procollagen into colla gen, is another potential marker of disturbed connectivetissue metabolism [8,9], High serum levels seem to reflect ongoing fibrosis in patients with chronic liver dis eases [10,11], Patients having acute renal failure [8] or various chronic renal disease [12] have also shown ele vated serum concentrations.…”
Section: Introductionmentioning
confidence: 99%